(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2014)
This article will discuss the problems arising from migration trends in Malaysia. The rising number of illegal immigrants has become an acute problem from both social and legal points of view, and must be given due attention by the authorities. The government has begun taking steps to deal with the issue of illegal immigrants in a more efficient manner. Among these is decreasing dependence on foreign workers, and increasing cooperation with sourcing countries, as well as other related parties. Attention should be given to strict two way enforcement at the border areas and the imposition of stringent punishment in accordance with the law for offences relating to illegal immigrants, notwithstanding whether they are illegal immigrants or Malaysian citizens. Keywords: enforcement, illegal immigrants, legislation, migration, social aspects